The Use of ChatGPT AI on Students’ Translation at Higher Education Students - Maria Enjelina Debibilian; Sujarwo; Siti Nurul Haliza (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2026)
The purpose of this research is to analyse the use of ChatGPT AI in student translation activities. The participants of this study were nine sixth-semester students from the English Education study programme at Universitas Megarezky in the 2022/2023 academic year, selected using purposive sampling. This study employed a qualitative descriptive method. The data collection techniques used in this study were interviews and field notes. The data analysis techniques used in this study were data reduction, data presentation, and conclusion drawing. Based on the results of the study, it shows that students consider ChatGPT to be very helpful and effective as a translation tool because of its speed, accuracy, easy and responsive interface, and ease of access in finding information and ideas for academic tasks such as translation. However, students are concerned that if ChatGPT is used too often without being balanced with good awareness, it will definitely lead to excessive dependence. This research concludes that balance is key in the use of ChatGPT for translation.